From buffet to best-fits: co-identifying and prioritizing best-bet CSA practices for targeting and scaling and Central Highlands of Ethiopia - Tamene, Lulseged D.; Abera, Wuletawu; Admassu, Zenebe (2021)
Recent evidences and developments highlight that climate-smart agriculture (CSA) is best placed to support the growing global populations under the world of land degradation and climate change while sustaining the environment and reducing emissions. It is considered progress and sustainable approach designed to link agricultural production and food security to climate change adaptation and mitigation, in order to guide the management of agriculture and food systems at multiple scales. Implementation and scaling of CSA practices/technologies/options are however resource and knowledge intensive exercises. CSA is also site-specific whereby what can be defined as ‘climate-smart’ in one location may not be smart in other context. It thus requires identifying practices and technologies that fit the landscape conditions under consideration and are profitable to and acceptable by the respective local communities. Climate-smart interventions need also consider local social differences, particularly gender and economic inequalities, to ensure equal benefits for men, women, and marginalized groups and to avoid exacerbating existing discriminations as well as be effective and sustainable. Careful selection among suit of options that satisfy the needs and requirements of nature and society is thus crucial to get meaningful contribution from CSA and promote its adoption. Linkages with key actors and exploring institutional options for targeting and scaling are also of paramount importance to achieve implementation of CSA at landscape scale and maintain sustainability. In this roprt we highlighted major steps and processes that have been followed to identify basket of CSA technologies and identified short-list of best bets that fit the situations of the two CSVs: Godoberet and Doyogena landscapes in two contrasting farming systems of the highlands of Ethiopia. The approach employed a combination of tools such as participatory methods, expert consultations, literature review, and survey data to identify and prioritize key CSA practices that are location- and context-specific. Among a copendum of CSA options, the key five technologies short-listed for the two sites are soil bunds (combined with and Phalaris grass (Phalaris acquatica and tree Lucerne (Chamaecytisus palmensis)), gully stabilization (with on-site and off-site interventions), exclosure, in-situ water harvesting, and agroforestry are the most important ones. Soil bunds of different types integrated with biological options such as grasses and trees (depending on site characteristics) are the most widely used and studied. This is because of the multiple benefits these options can offer: increase income (mainly from grasses and trees), reduce erosion, enhance soil moisture, restore soil health, sequester more carbon in the soil and with trees above ground and serve as livestock feed among others. It is however important to note that the ‘prioritized CSA practices’ highlighted in this report should be considered with caution as multiple and complementary options are ‘profitable’ compared to single ones. In addition, coupling CSA options with other agroadvisories will be more relevant to address complex problems.